Peruanos en Córdoba: migraciones, talleres textiles y prácticas comunitarias - Magliano, Maria Jose (2017)
Based on the findings of an ethnographic research, this paper proposes to analyze the labor trajectories in “informal” garment workshops of Peruvian migrants who live in territories of urban relegation of Cordoba (Argentina), regarding their strategies to access the city and family reproduction. Moreover, it explores the community practices, as resources of local organization intended for self-management, mobilized in neighborhoods in connection with the development of garment workshops. This study shows how some processes that exceed migration itself –such as presence/absence (selective) of the State in urban spaces, informal labor networks and difficulties to access housing– are related to mobility and labor insertions, making it possible and stimulating the existence and proliferation of informal garment workshops in specific places of the city